Stopping nucleos(t)ide analogue treatment in Caucasian hepatitis B patients after HBeAg seroconversion is associated with high relapse rates and fatal outcomes. Issue 8 (2nd March 2018) - Van Hees, S.; Bourgeois, S.; Van Vlierberghe, H.; Sersté, T.; Francque, S.; Michielsen, P.; Sprengers, D.; Reynaert, H.; Henrion, J.; Negrin Dastis, S.; Delwaide, J.; Lasser, L.; et al.
Summary: Background: Stopping nucleos(t)ide analogues (NA) after hepatitis B e antigen (HBeAg) seroconversion is associated with high relapse rates in Asian patients, but data in Caucasian cohorts are scarce. Clinical course, outcomes and immunological aspects of chronic hepatitis B infections differ substantially between distinct ethnicities. Aim: The aim of this study was to determine relapse rates, factors predicting relapse and clinical outcomes after nucleos(t)ide analogue cessation in a large, predominantly Caucasian cohort of chronic hepatitis B patients with nucleos(t)ide analogue‐induced HBeAg seroconversion. Methods: This is a nationwide observational cohort study including HBeAg positive, mono‐infected chronic hepatitis B patients with nucleos(t)ide analogue‐induced HBeAg seroconversion from 18 centres in Belgium. Results: A total of 98 patients with nucleo(s)tide analogue‐induced HBeAg seroconversion were included in the study. Of the 62 patients who stopped treatment after a median consolidation treatment of 8 months, 30 relapsed. Higher gamma‐glutamyl transferase levels at both treatment initiation (HR 1.004; P = 0.001 per unit increment) and HBeAg seroconversion (HR 1.006; P = 0.013 per unit increment) were associated with an increased risk of clinically significant relapse in a multivariate Cox regression model. Treatment cessation led to liver‐related death in 2 patients, of whom one showed a severe flare. Of the patients who continued treatment after HBeAg seroconversion, none relapsed or developed severe hepatic outcomes. Conclusion: Treatment withdrawal in Caucasian chronic hepatitis B patients after nucleos(t)ide analogue‐induced HBeAg seroconversion results in viral relapses in more than half of patients with potential fatal outcomes. These real‐world data further lend support to preferentially continue NA treatment after HBeAg seroconversion until HBsAg loss. Abstract : Linked Content This article is linked to Ingiliz and Canbay paper. To view this article visit https://doi.org/10.1111/apt.14649 .